Strategi Manajemen pada Street Food Yolkee di Pusat Kuliner Pasar Lama Tangerang - Hana Nathasya (Universitas Tarumanagara, 2020)
The purpose of this research is to analyze IFE, EFE, IE Matrix on Yolkee, and to find the strengths and weaknesses using SWOT analysis, and to know the right management strategy that can applied by Yolkee using QSPM. The type of research used in this study is qualitative descriptive approach. The data used in this research is primary data. The collection of data obtained from the field reaserch and study of literature. Results of this study showed the IFE, EFE, IE Matrix, SWOT analysis of Yolkee, and the management strategies that can applied by Yolkee by using QSPM.